Intestinal protein absorption in malnourished mice with acute schistosomiasis mansoni - Haroldo S. Ferreira; Eridan M. Coutinho; Naide R. Teodósio; Claudia L. Cavalcanti; Maria de Jesus A. Samico (Memorias do Instituto Oswaldo Cruz, 1993)
Intestinal protein absorption was studied in undernourished albino Swiss mice with acute schistosomiasis mansoni. Undernutrition was induced by feeding mice with the Regional Basic Diet (RBD) ingested by human populations in Northeast Brazil, an experimental model previously developed in our laboratory. Weaning mice were infected with 40 cercariae and compared to undernourished non-infected mice and/or to infected mice fed a balanced control diet. Apparent and True Protein Absorption Coefficients were determined by nitrogen balance during five consecutive days ending at the 63rd day of the trial (acute phase of murine schistosomiasis). Fecal metabolic nitrogen (FMN) was determined after administration of a non-protein diet and was also calculated through linear regression. Our results showed a reduced protein absorption in non-infected RBD-fed mice as compared to mice fed a casein control diet. Infection with Schistosoma mansoni had apparently no effect on intestinal protein absorption in well-nourished mice. However, infection seemed to interfere with protein absorption in under-nourished animals, since the lowest absorption ratios have been detected among RBD-fed infected mice. A brief discussion is made on the advantages of using the method of linear regression for the determination of FMN.